TPACK sebagai solusi guru Sekolah Dasar untuk meningkatkan hasil belajar Tematik siswa di era pandemi Covid'19 - Tamba, Nurhanifa (Jurnal Ilmiah Aquinas, 2021)
Â Â COVID-19 is a disease outbreak that originated in China and spread rapidly throughout the world.COVID-19 spread in Indonesia in early March 2020. The spread of this virus caused losses to many countries, especially in the field of education, therefore TPACK is a solution for elementary school teachers to improve student thematic learning outcomes in the era of the covid'19 pandemic which is carried out online. . TPACK is a theoretical framework for integrating technology, pedagogy, and materials such as interactive powerpoints. Researchers collected data through interview observations, surveys and blended learning methods. This research is the third grade students of SD Negeri 157013 Sibabangun 5 Tapanuli Middle of the Academic Year 2021/2022. Sampling was done by purposive sampling technique. That is by taking two classes taught by the same teacher. The initial conditions were obtained from daily test 1 with an average value of 51.05 as the control class, namely conventional learning. While the average value is 91.32 as the experimental class, namely TPACKbased learning using interactive powerpoint. By mastering TPACK, elementary school teachers can present TPACK-based learning for example powerpoint, Lectora inspire, short videos and so on related to the material to be studied and become the best solution when learning is done online and in accordance with the industrial revolution 4.0 32 as an experimental class, namely TPACK-based learning using interactive powerpoints. By mastering TPACK, elementary school teachers can present TPACK-based learning for example powerpoint, Lectora inspire, short videos and so on related to the material to be studied and become the best solution when learning is done online and in accordance with the industrial revolution 4.0 32 as an experimental class, namely TPACK-based learning using interactive powerpoints. By mastering TPACK, elementary school teachers can present TPACK-based learning for example powerpoint, Lectora inspire, short videos and so on related to the material to be studied and become the best solution when learning is done online and in accordance with the industrial revolution 4.0